Pengembangan Media Pembelajaran Interaktif Berbasis PowerPoint pada Materi Sistem Pencernaan Manusia (IPAS Kelas IV SD) - Azzahra Restian Iryanto; Elly’s Mersina Mursidik; Hendra Erik Rudyanto (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The integration of interactive media in elementary education is essential to enhance students' understanding of complex science topics such as the human digestive system. This study aimed to develop an interactive PowerPoint-based learning media for the topic of the human digestive system in Science and Social Studies (IPAS) for fourth-grade elementary school students, as well as to determine the feasibility and practicality of the developed media. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SDN Tempuran 4, Ngawi Regency, involving elementary school students and classroom teachers. Data were collected through observations, interviews, documentation, expert validation questionnaires (media, material, and language experts), and user response questionnaires. The results indicated that the developed interactive PowerPoint-based learning media was highly feasible and practical for use in the learning process. This was evidenced by the validation scores from media experts (86%), material experts (71%), and language experts (98%). Furthermore, the media received highly positive responses from teachers (94%) and students (94%), both categorized as excellent. Therefore, the interactive PowerPoint-based learning media is considered effective in improving the quality of learning in elementary schools.